2021
DOI: 10.1002/art.41877
|View full text |Cite
|
Sign up to set email alerts
|

American College of Rheumatology Guidance for COVID‐19 Vaccination in Patients With Rheumatic and Musculoskeletal Diseases: Version 2

Abstract: Objective. To provide guidance to rheumatology providers on the use of coronavirus disease 2019 vaccines for patients with rheumatic and musculoskeletal diseases (RMDs).Methods. A task force was assembled that included 9 rheumatologists/immunologists, 2 infectious disease specialists, and 2 public health physicians. After agreeing on scoping questions, an evidence report was created that summarized the published literature and publicly available data regarding COVID-19 vaccine efficacy and safety, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
105
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 88 publications
1
105
0
Order By: Relevance
“…JKI should be interrupted for one week after each vaccine dose. The last update of the ACR guidance was even more restrictive by introducing discontinuation of mycophenolate for one week following each vaccine dose and of acetaminophen and non-steroidal anti-inflammatory drugs (NSAIDs) 24 h prior to vaccination [106]. However, the limits on the use of immunosuppressive drugs in the vaccination period have been based on very few studies on traditional vaccines, generally counterbalanced by a higher number of reports, which did not show any significant negative interference in the immune response to vaccines, thus providing an explanation of the divergent recommendations.…”
Section: Immunosuppressive/immunomodulating Therapy and Covid-19 Vaccinesmentioning
confidence: 99%
See 3 more Smart Citations
“…JKI should be interrupted for one week after each vaccine dose. The last update of the ACR guidance was even more restrictive by introducing discontinuation of mycophenolate for one week following each vaccine dose and of acetaminophen and non-steroidal anti-inflammatory drugs (NSAIDs) 24 h prior to vaccination [106]. However, the limits on the use of immunosuppressive drugs in the vaccination period have been based on very few studies on traditional vaccines, generally counterbalanced by a higher number of reports, which did not show any significant negative interference in the immune response to vaccines, thus providing an explanation of the divergent recommendations.…”
Section: Immunosuppressive/immunomodulating Therapy and Covid-19 Vaccinesmentioning
confidence: 99%
“…All the authorized COVID-19 vaccines can stimulate specific cellular immunity (Table 4) Moreover, immunosuppressive treatment has even been associated in some studies, with a protective effect on the cytokine release syndrome [112] observed in some cases of SARS-CoV-2 infection. All these considerations may explain the different evaluations by the different Scientific Societies/Colleges, including EULAR [104], ACR [105,106], and the Korean College of Rheumatology [113], which has an intermediate position compared to the other two. All agree on the inhibitory effect of CCS and anti-CD20 mAbs [114], either isolated or in combination.…”
Section: Immunosuppressive/immunomodulating Therapy and Covid-19 Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in these patients the infection risk may be even higher for both the altered regulation of the immune system itself and for the immunosuppressive effects of medications [8]. Indeed, vaccinations in this population are complicated by disease-modifying immunosuppressive agents or antirheumatic drugs (either conventional, targeted synthetic or biologicals), which modulate or suppress key targets of the immune system and potentially decrease the immunogenicity and e cacy of the vaccines [9]. However, there is scant available data on real-world cohorts of vaccinated subjects and very limited data about response to COVID-19 mRNA vaccines in patients affected by IMID.…”
Section: Introductionmentioning
confidence: 99%